EVALUASI WAKTU TUNGGU RESEP OBAT TERHADAP KEPUASAN PASIEN RAWAT JALAN DI INSTALASI FARMASI RUMAH SAKIT ASSYIFA KOTA TANGERANG - Ekadipta Ekadipta; Muhammad Zuhriyanto; Siti Nurahayu (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2022)
Hospital is an important health service center and is needed to meet health needs. This study aims to evaluate the waiting time for prescription non-concoction and concoction medicines based on the hospital's minimum service standards and their effect on general outpatient satisfaction at the Pharmacy Installation of RSIA Assyifa, Tangerang. This study used a descriptive research design of outpatients who redeemed non-concoction and concoction medicines. Calculation of the waiting time for prescription services for non-concoction and concoction medicine is using a digital clock. Satisfaction was measured using a questionnaire which was analyzed multivariate. The samples taken in the study were 222 respondents. The results showed that the average waiting time for prescription of non-concoction medicine (8.9 minutes) and concoction medicine (16.6 minutes) had met the standards set by the hospital's SPM in the pharmaceutical sector according to the Minister of Health of the Republic of Indonesia NO. 129 of 2008 and by RSIA Assyifa. The results in the multivariate analysis obtained t = 10.126 and the standard coefficient of 0.88, indicating that waiting time has a strong positive effect on patient satisfaction with prescription of non-concoction and concoction medicine services at RSIA Assyifa.